Acetylcholinesterase and Butyrylcholinesterase Inhibitory Activities of β-Carboline and Quinoline Alkaloids Derivatives from the Plants of Genus Peganum - Ting Zhao; Ke-min Ding; Lei Zhang; Xue-mei Cheng; Chang-hong Wang; Zheng-tao Wang (Journal of Chemistry)
It was reported that the main chemical constituents in plants of genus Peganum were a serial of β-carboline and quinoline alkaloids. These alkaloids were quantitatively assessed for selective inhibitory activities on acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) by in vitro Ellman method. The results indicated that harmane was the most potent selective AChE inhibitor with an IC50 of 7.11 ± 2.00 μM and AChE selectivity index (SI, IC50 of BChE/IC50 of AChE) of 10.82. Vasicine was the most potent BChE inhibitor with feature of dual AChE/BChE inhibitory activity, with an IC50 versus AChE/BChE of 13.68 ± 1.25/2.60 ± 1.47 μM and AChE SI of 0.19. By analyzing and comparing the IC50 and SI of those chemicals, it was indicated that the β-carboline alkaloids displayed more potent AChE inhibition but less BChE inhibition than quinoline alkaloids. The substituent at the C7 position of the β-carboline alkaloids and C3 and C9 positions of quinoline alkaloids played a critical role in AChE or BChE inhibition. The potent inhibition suggested that those alkaloids may be used as candidates for treatment of Alzheimer’s disease. The analysis of the quantitative structure-activity relationship of those compounds investigated might provide guidance for the design and synthesis of AChE and BChE inhibitors.